The influence of sporting motivation and emotional state on the performance of volleyball players - Namazova, V.B. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the impact of athletic motivation and emotional state on volleyball players’ performance. 32 athletes aged 18-23, with at least a first-category qualification, participated in the study. The SMS-II questionnaire, POMS and SAN methods, and an analysis of game statistics were used. It was found that high intrinsic motivation and an optimal emotional state are associated with increased performance efficiency and a reduction in errors. Methods and structure of the study. A study of the influence of sports motivation and emotional state on the performance of volleyball players was conducted as part of a comprehensive psychological and pedagogical analysis. The study used methods of quantitative and qualitative analysis of the psychological characteristics of athletes, as well as analysis of their competitive activities. The study involved 32 athletes from men’s volleyball teams aged 18-23, with a sports qualification of at least I category, undergoing regular training and competitive preparation. All participants were informed about the objectives of the study and gave their consent to participate. Results and conclusions. Data processing revealed statistically significant correlations between motivational parameters and game performance indicators, which is consistent with the findings of a number of recent studies in the field of sports psychology. The study established a significant influence of sports motivation and emotional state on the game performance of volleyball players. The data obtained confirm that internal motivation is the leading factor ensuring greater involvement in the training process, resistance to competitive stress, and stability of game actions. Athletes with strong internal motivation demonstrated higher accuracy in attacks, more effective defensive actions, and fewer technical errors.